Histone methyltransferase ATX1 dynamically regulates fiber secondary cell wall biosynthesis in Arabidopsis inflorescence stem. Issue 1 (17th December 2020) - Wang, Xianqiang; Wang, Denghui; Xu, Wenjian; Kong, Lingfei; Ye, Xiao; Zhuang, Qianye; Fan, Di; Luo, Keming
Abstract: Secondary wall thickening in the sclerenchyma cells is strictly controlled by a complex network of transcription factors in vascular plants. However, little is known about the epigenetic mechanism regulating secondary wall biosynthesis. In this study, we identified that ARABIDOPSIS HOMOLOG of TRITHORAX1 ( ATX1 ), a H3K4-histone methyltransferase, mediates the regulation of fiber cell wall development in inflorescence stems of Arabidopsis thaliana . Genome-wide analysis revealed that the up-regulation of genes involved in secondary wall formation during stem development is largely coordinated by increasing level of H3K4 tri-methylation. Among all histone methyltransferases for H3K4me3 in Arabidopsis, ATX1 is markedly increased during the inflorescence stem development and loss-of-function mutant atx1 was impaired in secondary wall thickening in interfascicular fibers. Genetic analysis showed that ATX1 positively regulates secondary wall deposition through activating the expression of secondary wall NAC master switch genes, SECONDARY WALL-ASSOCIATED NAC DOMAIN PROTEIN1 ( SND1 ) and NAC SECONDARY WALL THICKENING PROMOTING FACTOR1 ( NST1 ). We further identified that ATX1 directly binds the loci of SND1 and NST1, and activates their expression by increasing H3K4me3 levels at these loci. Taken together, our results reveal that ATX1 plays a key role in the regulation of secondary wall biosynthesis in interfascicular fibers during inflorescence stem development of Arabidopsis .